Digital combination lock for car / Mohd Suhaimi Mohd Kamal and Mohd Shahid Osman - Mohd Kamal, Mohd Suhaimi; Osman, Mohd Shahid (2006)
As we know, common application like in factory. office and education can shows the higher technology that we can make. " Digital Combination Lock For Car” is used for car especially to start the car’s engine. It has a code numbers. When you use this project, you can start me car without key. Jhe circuit uses only 4 digit numbers. The user must enter the correct code. 4 digit number must be programmed as required before it can be used or function. When wrong numbers are entered, the circuit will be automatically locked in 15 minutes The reset button (e) will clear the wrong numbers. This circuit uses only s timer IC’s. Each timer is used for one code only. Four timers are used for coding purpose and the remaining timer will reset the wrong code.